(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2017)
This article examines the theme of Alonso Quijano Syndrome in Juan Bonilla’s short narrative. The article departures from the analysis of the concept of Alonso Quijano Syndrome through some short stories of Bonilla, in order to understand how he utilizes intertextuality, and how Alonso Quijano syndrome constitutes a vehicle which provides meaning as well as organizes the internal structure of Bonilla’s narrative. Alonso Quijano Syndrome theme is based in intertextuality which is understood as an unifying as well as a stylistic tool. Intertextuality beatifies the texts, actualize them, and, at the same time, immerses them into fiction, thereby providing them irony and humour.